Jornalismo colaborativo em redes digitais: estratégia comunicacional no ciberespaço. O caso de Zero Hora.com - Belochio, Vivian de Carvalho (2009)
This study was based in the idea that digital participative systems lead to changes in the institutionalized territory of journalism. The search for evidences of this process begins in the first chapter, with the analysis of journalism as an institutionalized territory and the processes of deterritorialization, reterritorialization and unterritorialization. Next, the technological changes that facilitated the origins of the information long tail are highlighted, which comprehends since the database up to the locative media and the mobile technologies. Then, it is identified the Pro-Am movement, characterized by the relation between professionals and laypeople. The second chapter focuses on the collaborative journalism in the networks as a communication strategy. At this point, the collaborative sections are defined. It is considered the four generations of digital journalism, influenced by the strategic adaptation of traditional media to the long tail of information. Consequently, the open collaborative pages were originated and became wide used. The information in the literature review is discussed taking into account the data from the case study. Thus, it was possible to identify some communication strategies from Zero Hora. com, based in the collaborative products. One concluded that works in partnership between professionals and fans in the digital periodical occur. The Pro-Am if only establishes, that in shy way. If it cannot affirm that it occurs, in Zero Hora.com, the unterritorialization, however strong marks of the process had been identified.